2018
DOI: 10.3390/act7020029
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary-Based BEL Controller Applied to a Magneto-Rheological Structural System

Abstract: This work addresses the problem of finding the best controller parameters in order to improve the response of a single degree-of-freedom structural system under earthquake excitation. The control paradigm considered is based on brain emotional learning (BEL) and the actuation over the building dynamics is carried out by changing the stiffness of a magneto-rheological damper. A typical BEL-based controller requires the definition of several parameters which can prove difficult and non-intuitive to obtain. For t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 35 publications
(38 reference statements)
0
7
0
Order By: Relevance
“…The use of PSO for computing the parameters of a building vibration BELBIC controller has already been explored in one of the authors previous works [17]. In the referred work, it was shown that this approach led to a set of controller parameters, that were able to outperform an empirical parameters selection method, based on trial-and-error.…”
Section: Results Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of PSO for computing the parameters of a building vibration BELBIC controller has already been explored in one of the authors previous works [17]. In the referred work, it was shown that this approach led to a set of controller parameters, that were able to outperform an empirical parameters selection method, based on trial-and-error.…”
Section: Results Discussionmentioning
confidence: 99%
“…Since then, this control strategy has been applied in a myriad of distinct engineering problems. For example in [16,17] a BEL controller performance was applied to semi-active vibration control and [34] have used BELBIC to control the voltage tracking in a boost converter. In [35] a sliding mode control-based on BELBIC was tested over robotic manipulators.…”
Section: The Bel-based Control Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…45 BELBIC Applications. Braz César et al 82 developed a BELBIC combined with PSO algorithms for the seismic vibration control of single storey building subjected to seismic loading and the actuating mechanism is incorporated through MR damper. Their proposed PSO optimized controller has shown higher performance in achieving control objectives.…”
Section: Brain Emotional Learning-based Intelligent Controllermentioning
confidence: 99%
“…Notably, the PSO tuning enhanced the controller's efficiency by almost 20%, far better than the traditional empirically tune controller. Braz César et al 82 developed PSO optimized BELBIC for the single-storey building structure subjected to seismic loading, and the actuating mechanism is supported by MR damper. In addition, their proposed PSO optimized controller has shown higher performance in achieving control objectives.…”
Section: Meta-heuristic Algorithms-based Hybrid Aic Controllersmentioning
confidence: 99%